Content of E.Coli, Coliform and Iron (Fe) Bacteria with A Refill Drinking Water Treatment System in Tinggimoncong District - Toalu, Apdiyani; Tawil, Muh. Risal; Musfirah, Musfirah; Marpaung, Mauritz Pandapotan; Pannyiwi, Rahmat; Halimatussa'diah, Halimatussa'diah (International Journal of Health Sciences, 2023)
Drinking water is water that has gone through a processing process or without a processing process that meets health requirements and can be drunk directly. Drinking water is safe for health if it meets the Physical, Microbiological, Chemical and Radioactive requirements contained in the mandatory parameters and additional parameters. The purpose of this study was to determine the content of E.coli, Coliform and Iron (Fe) Bacteria with a Refill Drinking Water Treatment System in Tinggimoncong District. This type of research is quantitative research with a descriptive approach, namely the type of research used to analyze data by describing or describing the data that has been collected as it is. This sampling technique is total sampling. This research was conducted on August 12-13 2022. The sample in this study was refill drinking water in Tinggimoncong District. In examining the laboratory test, the researcher used the Sanitarian Kit. Drinking water samples were taken from 11 drinking water depots spread across Tinggimoncong District. The results of this study indicated that of the 11 samples of drinking water that did not contain E.coli, and 7 samples of drinking water that contained coliform, 11 samples contained iron (Fe) according to the permissible levels and 4 samples of drinking water were free of microbiological and chemical content. From the results of this study, it is suggested that the Health Service and Community Health Centers improve supervision of the quality of DAMIU not only checking the quality of AMIU but also the feasibility of DAM and PHBS of employees and DAMIU quality is not only checked on processed products but on DAMIU that is ready to be distributed because contamination can occur during packaging.